An empirical study of the factors influencing the cultural adjustment of undergraduate Chinese international students to the United States - Hurny, Gina L., author; Kuk, Linda, advisor; Aoki, Eric, committee member; Rankin, Susan, committee member; Strathe, Marlene, committee member (Colorado State University. Libraries, 2014)
This quantitative study examined the factors that influence the cultural adjustment of undergraduate Chinese international students to the United States. The ever-increasing Chinese student population has forced colleges and universities to employ new strategies designed to ease the transition of Chinese students to life in the U.S. Chinese students have more difficulties in their adaptation and adjustment to U.S. culture and campus life than any other population of international students. Astin's (1993) Input-Environment-Output (I-E-O) model was adapted in an effort to provide a visual snapshot of the relationship between the factors and cultural adjustment. Gender, academic major, time in the United States, English language proficiency, and cultural values were measured to determine their influence on three constructs; acculturative stress, social and academic expectations and adjustment, and campus preparedness. Cultural adjustment was measured by intent to persist. Using an online survey data were collected from undergraduate Chinese international students at a large, public university in the mid-Atlantic region of the United States. Results suggested that English language proficiency is the single-most significant factor influencing the cultural adjustment challenges faced by Chinese international students. Implications for campus preparedness and recommendations for future research are discussed.
Keywords: academic adjustment; acculturation; Chinese international students; cultural adjustment; English language proficiency; social adjustment